2015
DOI: 10.4317/jced.52284
|View full text |Cite
|
Sign up to set email alerts
|

Haemostatic agents on the shear bond strength of self-adhesive resin

Abstract: Background Dentin surface contaminated with haemostatic agents can interfere with the bonding of self-adhesive resin cement. Therefore the purpose of this study was to evaluate the effect of various haemostatic agents such as Aluminium chloride, Ferric sulphate and Tannic acid on the shear bond strength of self-adhesive resin luting agent. Material and Methods The buccal surfaces of extracted premolars were flattened to expose the dentine. The teeth were then randomly divided into four groups. In Group I Alum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…However, some of these agents may lessen the bond strength of dental adhesives. 48 Mostly, these agents were applied around the gingiva T A B L E 3 (Continued) as bleeding occurs around the gingival margin. 49 Previous reports have shown that aluminum chloride and ferric sulfate dentin contamination can significantly lowered the bond strength of SE adhesive when compared to normal dentin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some of these agents may lessen the bond strength of dental adhesives. 48 Mostly, these agents were applied around the gingiva T A B L E 3 (Continued) as bleeding occurs around the gingival margin. 49 Previous reports have shown that aluminum chloride and ferric sulfate dentin contamination can significantly lowered the bond strength of SE adhesive when compared to normal dentin.…”
Section: Discussionmentioning
confidence: 99%
“…Hemostatic agents like aluminum chloride, ferric sulfate, and tannic acid can be used to control the bleeding. However, some of these agents may lessen the bond strength of dental adhesives 48 . Mostly, these agents were applied around the gingiva as bleeding occurs around the gingival margin 49 .…”
Section: Discussionmentioning
confidence: 99%
“…The calcium ions present in the hydroxyapatite crystals of enamel and dentin are replaced by aluminium ions present in the hemostatic agent which inhibits the effective demineralization of these tissues. Decrease in bond strength may be attributed to deposition of aluminium in the form of unbound minerals on the dentin surface forming a residual layer leading to decreased adhesive infiltration into dentin thereby impeding the bonding procedures [8].…”
Section: Discussionmentioning
confidence: 99%
“…However, rinsing alone cannot eliminate surfaces contamination and thus the remnant FS interfered with diffusion of adhesive in dentinal tubules. [ 31 32 ] Because of the weak acidity of the primer in self-etch adhesives, they could not dissolve the contamination by ViscoStat ® ;[ 33 ] hence, it is impossible to penetrate deeper into dentin. [ 32 ] The suggested mechanism was that hemostatic agent causes derangement in bonding procedure because of dentinal tubules obturation and dentinal surface was demineralized in different values.…”
Section: Applications Of Ferric Sulfate In Dentistrymentioning
confidence: 99%